What is product design. - Slack, Laura, ....- (Mies : Rotovision, 2006)
This unrivalled handbook is a guide to the world of industrial design, exploring what constitutes successful design, how it works, and how product design creates a market for itself. It explores the multifarious role of product designers, as new technology and materials present new possibilities for both form and function. What is Product Design? looks at issues of longevity and life cycles, multifunctionalism, concept generation and product development, prototyping, naming, and product placement. What is Product Design? is not just an in-depth exploration of successful design, it is also a stunning, diverse portfolio of cutting-edge work from designers and studios throughout the globe, showcasing world-beating design that exceeds the brief, and demands attention. Like the other titles in the Essential Design Handbooks series, this will be necessary reading for all professional graphic designers and students.
Keywords: Ontwerpen